WETTABILITY STUDIES OF SANDSTONE AFTER THE INJECTION PROCESS OF SURFACTANT BY OBSERVING SALINITY EFFECT, SURFACTANT CONCENTRATION AND TEMPERATURE - Muhammad Agus Sahputra; Sugiatmo Kasmungin; Muh. Taufiq Fathaddin (Lembaga Penelitian Universitas Trisakti, 2017)
The background of this research was based on residual of oil or residual saturationexperienced by irrigated rocks or oil recovery in the secondary oil recovery phase, so anEnhanced Oil Recovery (EOR) method is necessary. However, at that phase also stillfound the remaining oil that remains attached to rocks. Thus, the study of residual oil isrequired by wettability using variations of surfactant chemical solutions at roomtemperature conditions and reservoir temperature variations. Therefor the objectives ofthis research, the processing injection surfactant, interfacial tension of oil-water would bereduced. But, the oil cannot be swept at all in the reservoir by surfactant injection(tendency fluid to adhere rocks). This research will particularly discuss about study ofwettability in sandstones to examine the maximum sweeping point of area by combinationof surfactant and brine. Data analysis used in this research was brine and anionicsurfactant Alpha Olefin Sulfonate (AOS) and core. The specific concentrations of brineand surfactant such as 2000 ppm, 4000 ppm, 6000 ppm, 8000 ppm, 10000 ppm, and15000 ppm and 1.0%, 1,2%, 1,4%,1,6% 1,8% and 2,0%. Both of them will examine intemperature 300C, 700C, 800C, and 900C.The result shows of three cores (M1, M2, andM3) of this research get the porosity of each other such as 21,5%, 17,8%, and 20,3% withthe permeability such as 232 mD, 74 mD, and 185 mD. The category owned by porosityand permeability of each cores is very good. The wettability that very dominant categoryof each surfactant owned by mixed surfactant 2% with salinity 2000 ppm that have chosenby 36 mixed of surfactant in temperature 300C, 700C, 800C, and 900C. But, for mixsurfactant in salinity 15.000 ppm would cause the wettability down from water-wet tointermediate-wet. Therefore, the wettability can be concluded that the wettability would getinfluence by passed of certain salinity of fluid or surfactant and the wettability would riseby temperature